Isolation and Characterization of Cryptococcus neoformans from Environmental Sources in Busan - Oh, Kwang Seok (The Korean Society of Mycology, 2005)
Twenty nine samples of pigeon droppings (n = 12) and soil contaminated with avian excreta (n = 19), collected from different sites in Busan, were examined for isolation and characterization of Cryptococcus neoformans. Of these samples, 5 strains of C. neoformans were recovered from pigeon droppings (5/12 : 41.7%). All isolates were belonged to C. neoformans var. grubii (serotype A). The extracellular enzyme activities of the strains by using the API-ZYM system showed two different enzymatic patterns. The genetic variability among C. neoformans isolates was analyzed by random amplified polymorphic DNA (RAPD) using three 10-mer primers. Two different RAPD patterns, which clearly distinguished the isolates, were identified. Analysis of RAPD patterns provided a good characterization of environmental strains of C. neoformans serotype A as a heterogeneous group and were in good agreement with enzymatic profiles.